Réponses

2014-09-07T17:28:01+02:00
Bonjour

10/11 + 12/11 x 5/6 = 10/11 + 60/ 66 = 60/66 +60/66 = 120/132 = 10/11

(2/9 + 5/6) : 5/2 = (4/18 + 15/18) : 5/2 = 19/18 x 2/5 = 38/90 = 19/45

-4 -3 (-7) = -4 +21 = 17
13-4 sur -2+17 = 9 /15
2014-09-07T17:36:35+02:00
A = 10/11+ 12/11 x 5/6
A = 10/11 + 60/66
A = 10 x 6 / 11 x 6 + 60/66
A = 60/66 + 60/66
A = 120/66
A = 6 x 20 / 6 x 11
A = 20/11

B = (2/9 + 5/6) / 5/2
B = (2 x 2 / 9 x 2 + 5 x 3 / 6 x 3) / 5/2
B = (4/18 + 15/18) / 5/2
B = 19/18 x 2/5
B = 38/90
B = 2 x 19 / 2 x 45
B = 19/45

C = 4 - 3 x (- 7)
C = - 4 + 21
C = 17

D = 13 - 4/2 + 17
D = 13 x  2 / 1 x 2 - 4/2 + 17 x 2 / 1 x 2
D = 26/2 - 4/2 + 34/2
D = 56/2
D = 2 x 28 / 2 x 1
D = 28/1
D = 28